Multiscale drivers of arthropod functional guilds in rice agroecosystems: Evaluating the roles of climatic, landscape, and management factors - Yu-Pin Lin; Pei-Chen Lin; Shafira Wuryandani; Chun-Chia Liu; Chiao-Ming Lin; Chi-Wei Tsai; Chi-Lun Huang; Chuan-Kai Ho; Gerard H. Ros (Agriculture, Ecosystems & Environment, 2026)

Chlorpyrifos exposure induces inflammatory and immune dysregulation: An integrative in silico and in vitro analysis - Chen-Yu Chiang; Shih-Pin Chen; Ci-Wen Luo; Chun-Hung Su; Shiuan-Shinn Lee; Wen-Ying Chen; Chun-Jung Chen; Ching-Chi Tseng; Pin-Tzu Chen; Yin-Che Lu; Yu-Hsiang Kuan (Pesticide Biochemistry and Physiology, 2026)

Targeting the NOX4/NLRP inflammasome axis confers protection by isoliquiritigenin against H2O2-induced synovial inflammation - Yu-Chun Chang; Wei-Wen Kuo; Yen-Pin Chen; Shih-Wen Kao; Dennis Jine-Yuan Hsieh; Tsung-Jung Ho; Chia-Hua Kuo; Chien-Yao Fu; Chih-Yang Huang; Shinn-Zong Lin (Chemico-Biological Interactions, 2026)

Self-healing chitosan-catechol hydrogel with tailored self-assembled fibrillar or micellar structures for biomedical applications - Pin-Yu Chen; Yuxuan Zhang; Shan-hui Hsu (Carbohydrate Polymers, 2026)

A digital-enabled circular recovery system for post-consumer inhalers: Linking material recovery, behaviour, and carbon reduction - Huong Thanh Hoang; Luong Cao Tung Son; Yu-Fen Huang; Ren-Hao Pan; Phuong Truc Nguyen Le; I-Chun Chuang; Huang-Chi Chen; Hung-Pin Tu; Chih-Hsing Hung; Da-Wei Wu (Journal of Cleaner Production, 2026)

Mapping climate-conditioned PM2.5 response under climate change in Taiwan using a high-resolution Geo-AI model - Pei-Yi Wong; Wei-Lun Hsu; Chieh-Ying Chen; Chien-Fei Chen; Chia-Wei Hsu; Shih-Chun Candice Lung; Ta-Chih Hsiao; Chia-Pin Yu; Wan-Yu Liu; Pau-Chung Chen; Wei Jie Seow; Chien-Hao Sung; et al. (Journal of Environmental Management, 2026)

Type I IFNs, IFNc, IFNd1, IFNd2, IFNh, and type II IFNs, IFN-γ and IFN-γrel, and their possible receptors with the identification of two variants of IFNc and IFNh in turbot (Scophthalmus maximus) - Bo Li; Meng Xin Yan; Yu Hang Deng; Xiao Qian Jiao; Shan Nan Chen; Xu Jia Zhang; Jia Le Chen; Xue Yun Peng; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Assessing the impact of climate variability on exposure indices of Portunid crabs in the Southern East China sea - Irene Chia Ling Lim; Yan-Lun Wu; Wei-Pin Hsu; Muhamad Naimullah; Wei-Yu Lee; Lu-Chi Chen; Kuo-Wei Lan (International Journal of Remote Sensing, 2026)

Inhibiting pyruvate carboxylase as a potential therapeutic strategy for alleviating rheumatoid arthritis - Szu-Wei Huang; Hui-Chun Yu; Hsien-Bin Huang; Pin-Chen Chen; Ming-Chi Lu (Inflammopharmacology, 2026)

Design Rules for Robust Coronary Artery Segmentation: A Systematic Analysis of Dataset Size, Windowing, Architectures, and Vessel Geometry - Ming-Hui Hung; Yu-Wei Chiang; Hao-Yun Liu; Han-Hsuan Chu; Yu-Sen Huang; Pin-Yi Chiang; Hsin-Ming Chen; Tzung-Dau Wang; Shyh-Jye Chen; Wen-Jeng Lee (Annals of Biomedical Engineering, 2026)

Machine learning and spatial regression approaches to estimating willingness to pay for ecosystem services in Jakarta and Taoyuan - Shafira Wuryandani; Yu-Pin Lin; Pei-Chen Lin; Dirk S. Schmeller; Gerard H. Ros (Ecosystem Services, 2026)

Social behavior of masked palm civet in an urban habitat - Po-Jun Chuang; Pin Xuan Lim; Shan-Min Chen; Pin-Huan Yu; Wei-Ting Liu; Hui-Yun Tseng (Mammal Research, 2026)

Protective effects of sodium benzoate against toluene-induced reward enhancement, behavioral disturbances, and impaired synaptic plasticity in mice - Chung-Pin Hsieh; Mei-Yi Lee; Chia-Yu Lin; Ming-Huan Chan; Hwei-Hsien Chen (NeuroToxicology, 2026)

Widely targeted metabolomics reveals chemical mechanism of bloating in Rosa roxburghii Tratt juice induced by vitamin C and its chiral isomers - Hong Yang; Yuting Liu; Xinying Wang; Wenxin Zhang; Bo Peng; Dalong Chen; Angze Gao; Weixin Huang; Pin Qian; Deshun Yu; Yifu Tian; Xianzhi Dong (Food Chemistry, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Closed-loop recycling and recovery of vanadium cathodes from waste aqueous zinc-ion batteries - Hsing-Kai Tseng; Jun-An Su; I-Mao Chen; Yu-Ze Chen; Jun-Yi Wu; Pin-Han Chen; Fan-Wei Liu (Chemical Engineering Journal, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

Genomic, transcriptional and proteomic clarification of fathead minnow and common carp composition in epithelioma papulosum cyprini (EPC) cell line - Bo Li; Jing Hao Yuan; Yu Hang Deng; Shan Nan Chen; Meng Yao Ji; Xu Jia Zhang; Yang Liu; Zhen Gan; Pin Nie; Lan Hao Liu (Fish & Shellfish Immunology, 2026)

Detection of Marteilioides chungmuensis in cultured Portuguese oyster (Crassostrea angulata) in southern Taiwan - I-wen Chen; Chieh-Hao Wu; Yi-Pin Lu; Yu-Ju Lin (Fish & Shellfish Immunology, 2025)

Peroxymonosulfate activation by iron-sulfur tailings doped with SiO2 for efficient degradation of tetracycline - Chen-Chen Yin; Chun Cheng; Peng-Yu Zhang; Zheng-Yuan Zhang; Ying Qin; Li-Pin Xue; Yu-Qi Feng; Bai Sun; Shu-guang Zhu (Environmental Science and Pollution Research, 2025)

Seismic evidence for magmatism-driven mud volcanism in the northern continental margin of the South China Sea - Junhui Yu; Pin Yan; Yanlin Wang; Guangjian Zhong; Changliang Chen (Marine and Petroleum Geology, 2025)

Dramatically suppressed climate signals in the Yellow River - Yonggui Yu; Rick J. Yang; Gang Wang; Jaap H. Nienhuis; Xianyao Chen; James T. Liu; Marcel van der Perk; Rens van Beek; Xuefa Shi; Shuqing Qiao; Zhi Li; Jay Lee; et al. (Global and Planetary Change, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Hydraulic heterogeneity estimation with transient hydraulic tomography and convolutional encoder-decoder neural network - Yu-Kai Chen; Jui-Pin Tsai; Bo-Tsen Wang; Chia-Hao Chang (Stochastic Environmental Research and Risk Assessment, 2025)

Deciphering the miRNA–mRNA Interaction Network Regulating Aging Skeletal Muscle in Various Exercise Regimens through Comprehensive Bioinformatics Analysis - Zhi Yu; Pin-Shi Ni; Zhuang-Zhi Wang; Zheng-Yang Zhao; Bao-Yi Chen; Zhen-En Zhang; Fang-Hui Li (Cell Biochemistry and Biophysics, 2025)

Enhanced SERS performance through defect-guided growth of 2D/3D AuAg nanoplates for chemical sensing and cellular imaging applications - Kuan-Wen Liu; Pei-Yu Sie; Hsi-Ying Chen; Fong-I Ho; Po-Sheng Huang; Pin Chieh Wu; Mei-Yi Liao (Analytica Chimica Acta, 2025)

A Comprehensive Investigation of Physics-Informed Learning in Forward and Inverse Analysis of Elastic and Elastoplastic Footing - Xiao-Xuan Chen; Pin Zhang; Zhen-Yu Yin (Computers and Geotechnics, 2025)

Sacrificial reduction effects derived inorganic-rich hybrid solid electrolyte interfaces for long-term and high reversibility aqueous zinc-ion batteries - Yu Chen; Jiahong Fan; Qian Li; Pin Yi; Houfu Tu; Dedong Shan; Wentao Wang; Shulin Zhao; Yang Zhang; Yuping Wu; Yuhui Chen; Dengji Xiao (Chemical Engineering Journal, 2025)

Kirenol ameliorates endotoxin-induced acute lung injury by inhibiting the ERK and JNK phosphorylation–mediated NFκB pathway in mice - Frank Cheau-Feng Lin; Shih-Pin Chen; Sheng-Chien Lin; Ching-Chi Tseng; Stella Chin-Shaw Tsai; Yu-Hsiang Kuan (Inflammopharmacology, 2025)

Enrichment and characterization of foodborne fungal spores by ferric ion-based surface-assisted laser desorption/ionization mass spectrometry - Tzu-Ling Yang; Chih-Wei Chen; Noor Hidayat Abu Bakar; Pin-Chen Pan; Po-Hung Cheng; Yu-Chie Chen (Food Chemistry, 2025)

Effects of forest bathing and the influence of exposure levels on cognitive health in the elderly: Evidence from a suburban forest recreation area - Jittakon Ramanpong; Chen Tsao; Jie Yin; Chih-Da Wu; Yu-Chih Huang; Chia-Pin Yu (Urban Forestry & Urban Greening, 2025)

The difference in roaming behavior between owned and unowned dogs in a satoyama landscape area - Tsung-Han Kuo; Gau-Ming Chang; Pin-Huan Yu; Wei-Hsuan Chen; Shih-Ching Yen (Applied Animal Behaviour Science, 2025)

Metal ions-mediated concerted electron-proton transfer enables catalytic oxidation of phenolic contaminants by permanganate - Tiansheng Chen; Pin Xie; Yanghai Yu; Xiaoguang Duan; Yuankui Sun; Xiaohong Guan (Water Research, 2025)

Parafrigoribacterium soli sp. nov. and Parafrigoribacterium humi sp. nov., two novel siderophore-synthesizing species isolated from black soil - Yu-Ting OuYang; Le-Bin Chen; Jian-Yu Jiao; Zi-Xuan Hu; Jiong-Shan Wang; Tian-Hang Yang; Jun Xiao; Ting-Ting She; Pin-Jiao Jin; Shuang Wang; Lan Liu; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Sedimentary Signatures of Super Typhoon Haiyan: Insight from Core Record in South China Sea - Yu-Huang Chen; Chih-Chieh Su; Pai-Sen Yu; Ta-Wei Hsu; Sheng-Ting Hsu; Hsing-Chien Juan; Yuan-Pin Chang; Yu-Fang Ma; Shye-Donq Chiu (Journal of Marine Science and Engineering, 2024)
Sedimentary records of event deposits are crucial for regional natural disaster risk assessments and hazard history reconstructions. After Super Typhoon Haiyan passed through the South China Sea in 2013, five gravity cores were collected along the typhoon path in the southern South China Sea basin (>3800 mbsl). The results showed that Super Typhoon Haiyan deposits with clear graded bedding are preserved at the top of all cores. The thickness of the typhoon layers ranges from 20 to 240 cm and is related to changes in typhoon intensity. The lack of river-connected submarine canyon systems limited the transportation of terrestrial sediments from land to sea. Super Typhoon Haiyan-induced large surface waves played an important role in carrying suspended sediment from the Philippines. The Mn-rich layers at the bottom of the typhoon layers may be related to the soil and rock composition of the Palawan region, which experienced tsunami-like storm surges caused by Super Typhoon Haiyan. These Mn-rich layers may serve as a proxy for sediment export from large-scale extreme terrigenous events. This study provides the first sedimentary record of extreme typhoon events in the deep ocean, which may shed light on reconstructing regional hazard history.

Sporelings and growth of the marine red alga, Gelidium elegans (Gelidiaceae), from Northern Taiwan - Showe-Mei Lin; Shih-Jhe Chen; Pin-Yu Huang; Li-Chia Liu; Yu-Shan Chiou (Journal of Applied Phycology, 2024)

Methylobacterium nigriterrae sp. nov., isolated from black soil - Le-Bin Chen; Yu-Ting OuYang; Lan Liu; Pin-Jiao Jin; Rong-Rong Huang; Wen-Yi Pan; Ying Wang; Jia-Ying Xing; Ting-Ting She; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Coral mariculture using abandoned abalone farming ponds in northeastern Taiwan - Shinya Shikina; Yin-Chu Cheng; Tzu-Chieh Lin; Yu-En Chang; Pin-Hsuan Tsai; Emma Chen; Yu-Chuan Chang; Yuen-Yi Leung; Yi-Chun Yu; Yi-Ling Chiu (Aquaculture, 2024)

Possible toxification mechanisms of acute and chronic pentachlorophenol to Montipora digitata: Limitation of energy supply and immunotoxicity - Lan Luo; Pengfei Xue; Xuan Chen; Pin Gan; Xiaoli Li; Kefu Yu; Yuanyuan Zhang (Science of The Total Environment, 2024)

Treatment of arsenic-contaminated groundwater with a novel iron oxide/carbon composite as the adsorbent - Hung-Hsiang Chen; Yu-Chen Chang; Wei-Kuo Wei; Yung-Pin Tsai; Chih-Chi Yang; Ku-Fan Chen (Water, Air, & Soil Pollution, 2024)

Bisphenol M inhibits mouse oocyte maturation in vitro by disrupting cytoskeleton architecture and cell cycle processes - Huilei Chen; Yang Liu; Yue Huang; Pin Zhang; Danli Du; Wenhua Yu; Caiyun Wu; Hongzhen Ruan; Ping Zhou; Zhiming Ding; Huifen Xiang (Reproductive Toxicology, 2024)

Effects of Attachment Design and Aligner Material on Mandibular Canine Distal Bodily Movement in Aligner Treatment - Pin-Yu Chen; Heng-Li Huang; Jian-Hong Yu; Jui-Ting Hsu (Journal of Medical and Biological Engineering, 2024)
Purpose Dental crowding is a result of a mismatch between tooth size and arch dimensions, which leads to malocclusion; treatment often involves premolar extraction before orthodontic alignment. Clear aligners are limited in their ability to achieve canine distal bodily movement, a common orthodontic maneuver. This study investigated the impacts of attachment design and aligner material on the efficacy of canine distal bodily movement. Methods A finite element analysis was conducted to examine the impact of various attachment designs and two aligner materials, thermoplastic polyurethanes/polycarbonate (TPU/PC) and polyethylene terephthalate glycol-modified (PETG), on mandibular canine distal bodily movement. The investigation focused on the biomechanical responses in the periodontal ligament (PDL) and surrounding alveolar bone. Results Attachment configuration exerted a strong influence on mandibular canine movement. Vertically oriented attachment pairs positioned mesially (mesial occlusal–mesial cervical) resulted in the most effective canine distal bodily movement, followed by a rectangular attachment. TPU/PC aligners induced slightly higher principal stresses in the PDL and von Mises stress and strain in the surrounding alveolar bone compared with PETG aligners; however, the difference was negligible, amounting to less than 6%. Conclusion Attachment design, specifically vertically oriented pairs positioned mesially (mesial occlusal–mesial cervical), was determined to be the crucial factor influencing the efficacy of canine distal bodily movement. The choice of aligner material (TPU/PC or PETG) has minimal impact on this orthodontic procedure.

Comparison of the inactivation of Uronema marinum in mariculture by UV/chlorine, UV/monochloramine, and UV/chlorine dioxide: Efficiency, mechanism and feasibility - Pin Gan; Xuan Chen; Yuanyuan Zhang; Xudong Li; Fangyu Liang; Tianhao Wu; Pengfei Xue; Kefu Yu (Journal of Water Process Engineering, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Analytical solution for transient radial interaction between energy piles and soils: Thermo-elastic cavity expansion analysis - He Yang; Pei-Zhi Zhuang; Pin-Qiang Mo; Hai-Sui Yu; Xiaohui Chen (Geomechanics for Energy and the Environment, 2024)

Incorporation of atomic Fe-oxide triggers a quantum leap in the CO2 methanation performance of Ni-hydroxide - Amisha Beniwal; Dinesh Bhalothia; Yin-Rong Chen; Jui-Cheng Kao; Che Yan; Nozomu Hiraoka; Hirofumi Ishii; Mingxing Cheng; Yu-Chieh Lo; Xin Tu; Yun-Wei Chiang; Chun-Hong Kuo; et al. (Chemical Engineering Journal, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Postvaccination serosurveillance of foot-and-mouth disease through virus-neutralizing and nonstructural protein antibody tests on pig farms in Taiwan: 2009–2020 - Ming-Chang Lee; Yu-Fen Sun; Ming-Chung Deng; Nien-Nung Lin; Jung-Pin Hsu; Chwei-Jang Chiou; Wen-Jane Tu; Shih-Ping Chen (Preventive Veterinary Medicine, 2024)

1300-m-High gas plume from pockmarks in the north Nansha waters, South China sea - Yanlin Wang; Guanghong Tu; Junhui Yu; Pin Yan; Jinfeng Ma; Zhuangcai Tian; Changliang Chen (Marine and Petroleum Geology, 2024)

Chlorpyrifos-induced suppression of the antioxidative defense system leads to cytotoxicity and genotoxicity in macrophages - Yin-Che Lu; Chen-Yu Chiang; Shih-Pin Chen; Yu-Wei Hsu; Wen-Ying Chen; Chun-Jung Chen; Yu-Hsiang Kuan; Sheng-Wen Wu (Environmental Toxicology and Pharmacology, 2024)

Unstable geomorphologic fabric impacted by excess magmas and propagating rifts in the central West Philippine Basin - Weidong Luo; Pin Yan; Gaowen He; Yufang Tan; Ruiying Ye; Hongjun Chen; Zhen Lin; Houjin Wang; Minghui Zuo; Changliang Chen; Junhui Yu; Yanlin Wang (Geomorphology, 2024)

The health risk reduction of PM2.5 via a green curtain system in Taiwan - Yi Hsing Chang; Ting-Hsuan Chen; Hsin-Ying Chung; Hsi-Yu Hsiao; Pin-Chieh Tseng; Yu-Chun Wang; Shih-Chun Candice Lung; Huey-Jen Su; Yaw-Shyan Tsay (Building and Environment, 2024)

The SMAC mimetic GDC-0152 is a direct ABCB1-ATPase activity modulator and BIRC5 expression suppressor in cancer cells - I-Li Lin; Yu-Ting Lin; Yung-Chieh Chang; Sree Karani Kondapuram; Kai-Hsuan Lin; Pin-Chen Chen; Chung-Ying Kuo; Mohane Selvaraj Coumar; Chun Hei Antonio Cheung (Toxicology and Applied Pharmacology, 2024)

Photochemical oxidation of VOCs and their source impact assessment on ozone under de-weather conditions in Western Taiwan - Manisha Mishra; Pin-Hsin Chen; Guan-Yu Lin; Thi-Thuy-Nghiem Nguyen; Thi-Cuc Le; Racha Dejchanchaiwong; Perapong Tekasakul; Shih-Heng Shih; Ciao-Wei Jhang; Chuen-Jinn Tsai (Environmental Pollution, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Assessment of sediment transport in Luxiapuqu watershed using RUSLE-TLSD and InSAR techniques: Yarlung Tsangpo River, China - Hao-Shuang Chen; Ling Lan; Yi-Pin Nie; Yu-Ge Wang; Xie-Kang Wang (Environmental Science and Pollution Research, 2024)

Exposure to pentachlorophenol destructs the symbiotic relationship between zooxanthellae and host and induces pathema in coral Porites lutea - Yuanyuan Zhang; Lan Luo; Pin Gan; Xuan Chen; Xiaoli Li; Yan Pang; Xiaopeng Yu; Kefu Yu (Science of The Total Environment, 2024)

Physiological and psychological responses to transitions between urban built and natural environments using the cave automated virtual environment - Di Chen; Jie Yin; Chia-Pin Yu; Shengjing Sun; Charlotte Gabel; John D. Spengler (Landscape and Urban Planning, 2024)

Subsurface structures and nature of seafloor mounds in the northern South China Sea margin: Implications for Mesozoic hydrocarbon exploration - Junhui Yu; Pin Yan; Yanlin Wang; Guangjian Zhong; Changliang Chen (Geomorphology, 2024)

Efficient degradation of fluoroquinolone antibiotics in the landfill leachate by sludge biochar activated peracetic acid: Radical vs non-radical process - Zilin Zhou; Yan Yang; Gang Xue; Yang Yu; Jiabin Chen; Pin Gao; Yajie Qian (Chemical Engineering Journal, 2024)

Branch distribution pattern and anticoagulant activity of a fucosylated chondroitin sulfate from Phyllophorella kohkutiensis - Di Lan; Jiali Zhang; Xiaolei Shang; Lijuan Yu; Chen Xu; Pin Wang; Lige Cui; Nanqi Cheng; Huifang Sun; Jianing Ran; Le Sha; Ronghua Yin; et al. (Carbohydrate Polymers, 2023)

Inactivation of Heterosigma akashiwo under UV/peroxydisulfate advanced disinfection system in marine waters - Xuan Chen; Kunling Huang; Pin Gan; Lan Luo; Kefu Yu; Yuanyuan Zhang; Yunfeng Pang; Pengfei Xue (Chemosphere, 2023)

Long-term detraining reverses the improvement of lifelong exercise on skeletal muscle ferroptosis and inflammation in aging rats: fiber-type dependence of the Keap1/Nrf2 pathway - Zhuang-Zhi Wang; Hai-Chen Xu; Huan-Xia Zhou; Chen-Kai Zhang; Bo-Ming Li; Jia-Han He; Pin-Shi Ni; Xiao-Ming Yu; Yun-Qing Liu; Fang-Hui Li (Biogerontology, 2023)

Source-apportionment and spatial distribution analysis of VOCs and their role in ozone formation using machine learning in central-west Taiwan - Manisha Mishra; Pin-Hsin Chen; Wilfredo Bisquera; Guan-Yu Lin; Thi-Cuc Le; Racha Dejchanchaiwong; Perapong Tekasakul; Ciao-Wei Jhang; Ci-Jhen Wu; Chuen-Jinn Tsai (Environmental Research, 2023)

Discrete element modelling of thermal penetration test with heating and cooling - Pin-Qiang Mo; Jing Hu; Yu-Chen Hu; Kuan-Jun Wang; Abolfazl Eslami; Liu Gao (Computers and Geotechnics, 2023)

Arginase from Priestia megaterium and the Effects of CMCS Conjugation on Its Enzymological Properties - Yu Liang Jiao; Pin Quan Shen; Shu Fang Wang; Jing Chen; Xiang Hong Zhou; Gui Zhen Ma (Current Microbiology, 2023)

Association between ambient air pollutant interaction with kidney function in a large Taiwanese population study - Wei-Yu Su; Da-Wei Wu; Hung-Pin Tu; Szu-Chia Chen; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Science and Pollution Research, 2023)

Ecofriendly removal of Lead, Cadmium and Arsenic along with turbidity from contaminated water using natural reservoir clay (NRC) and S. pasteurii derived urease - Jyoti Prakash Maity; Yung-Ping Chen; Jirawadee Promsri; Yi-Hsun Huang; Raju Kumar Sharma; Yu-Hui Chen; Pin-Yun Lin; Marut Tangwattanachuleeporn; Kulwara Poolpol; Tsung-Hsien Chen; Chien-Yen Chen (Desalination, 2023)

Estimating divergent forest carbon stocks and sinks via a knife set approach - Shitephen Wang; Keito Kobayashi; Satoru Takanashi; Chiung-Pin Liu; Dian-Rong Li; San-Wen Chen; Yu-Ting Cheng; Kai Moriguchi; Masako Dannoura (Journal of Environmental Management, 2023)

High-Fat Diet Exacerbates Autistic-Like Restricted Repetitive Behaviors and Social Abnormalities in CC2D1A Conditional Knockout Mice - Yu-Chiao Wang; Chin-Hao Chen; Cheng-Yi Yang; Pin Ling; Kuei-Sen Hsu (Molecular Neurobiology, 2023)

Origin of a giant fuzzy reflection zone and its implication for natural gas exploration in the southwestern Qiongdongnan Basin of the South China Sea - Junhui Yu; Pin Yan; Yanlin Wang; Yan Qiu; Guanghong Tu; Changliang Chen (Journal of Oceanology and Limnology, 2023)

Discovery of pockmarks in the Zengmu Basin, southern South China Sea and the implication - Yanlin Wang; Guanghong Tu; Junhui Yu; Pin Yan; Yongbin Jin; Changliang Chen; Jie Liu (Journal of Oceanology and Limnology, 2023)

Occurrence, spatial distribution, and sources of PFASs in the water and sediment from lakes in the Tibetan Plateau - Yu Chen; Lijia Wei; Wei Luo; Ning Jiang; Yali Shi; Pin Zhao; Bila Ga; Zhiguo Pei; Yingming Li; Ruiqiang Yang; Qinghua Zhang (Journal of Hazardous Materials, 2023)

Geophysical evidence for a serpentine mud volcano in the relict slow-spreading center of the South China Sea - Yanlin Wang; Pin Yan; Junhui Yu; Guanghong Tu; Jun Wang; Yan Qiu; Changliang Chen (Tectonophysics, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Paleolimnological evidence for lacustrine environmental evolution and paleo-typhoon records during the late Holocene in eastern Taiwan - Liang-Chi Wang; Yu-Min Chou; Huei-Fen Chen; Yuan-Pin Chang; Hong-Wei Chiang; Tien-Nan Yang; Liang-Jian Shiau; Yue-Gau Chen (Journal of Paleolimnology, 2022)

Magnetic porous biochar as a renewable and highly effective adsorbent for the removal of tetracycline hydrochloride in water - Hucheng Yang; Hao Yu; Jiahao Wang; Tao Ning; Pin Chen; Jing Yu; Siyuan Di; Shukui Zhu (Environmental Science and Pollution Research, 2021)

Effect of selected sampling media, flow rate, and time on the sampling efficiency of a liquid impinger packed with glass beads for the collection of airborne viruses - Yen-Chi Chen; I-Jen Wang; Chih-Ching Cheng; Yu-Chiao Wu; Chun-Hsuan Bai; Kuo-Pin Yu (Aerobiologia, 2021)

The Roles of Epinephelus coioides miR-122 in SGIV Infection and Replication - Hong-Yan Sun; Yu-Ling Su; Pin-Hong Li; Jia-Yang He; He-Jia Chen; Gang Wang; Shao-Wen Wang; Xiao-Hong Huang; You-Hua Huang; Qi-Wei Qin (Marine Biotechnology, 2021)
In mammals, mature miR-122 is 22 nucleotides long and can be involved in regulating a variety of physiological and biological pathways. In this study, the expression profile and effects of grouper Epinephelus coioides miR-122 response to Singapore grouper iridovirus (SGIV) infection were investigated. The sequences of mature microRNAs (miRNAs) from different organisms are highly conserved, and miR-122 from E. coioides exhibits high similarity to that from mammals and other fish. The expression of miR-122 was up-regulated during SGIV infection. Up-regulation of miR-122 could significantly enhance the cytopathic effects (CPE) induced by SGIV, the transcription levels of viral genes (MCP, VP19, LITAF and ICP18), and viral replication; reduce the expression of inflammatory factors (TNF-a, IL-6, and IL-8), and the activity of AP-1 and NF-κB, and miR-122 can bind the target gene p38α MAPK to regulate the SGIV-induced cell apoptosis and the protease activity of caspase-3. The results indicated that SGIV infection can up-regulate the expression of E. coioides miR-122, and up-regulation of miR-122 can affect the activation of inflammatory factors, the activity of AP-1 and NF-κB, and cell apoptosis to regulate viral replication and proliferation.

Eliminating vascular interference from the Spot Sign contributes to predicting hematoma expansion in individuals with spontaneous cerebral hemorrhages - Pan Yi; Min Xu; Pin Chen; Yu Luo; Dongdong Wang; Hui Wang; Cunzu Wang (Acta Neurologica Belgica, 2021)

Histopathology, Molecular Identification and Antifungal Susceptibility Testing of Nannizziopsis arthrosporioides from a Captive Cuban Rock Iguana (Cyclura nubila) - Yen-Han Chen; Meng-Jou Chi; Pei-Lun Sun; Pin-Huan Yu; Chen-Hsuan Liu; Jose F. Cano-Lira; Wen-Ta Li (Mycopathologia, 2020)

Feasibility of using bed filters packed with rice-straw-based activated carbon and selected biomass waste for the control of frying fume exhaust - Yen-Chi Chen; Xuan-En Yang; Kun-Yi Lin; Wei-Wen Huang; Chi-Chi Lin; Kuo-Pin Yu (Environmental Science and Pollution Research, 2020)

Flavobacterium ajazii sp. nov., Isolated from Seaweed of Gouqi Island, China - Ishrat Khan; Sanjit Chandra Debnath; Cen Yan; Can Chen; Yan Xu; Wen-Jie Wang; Yu-Chao Yu; Dao-Qiong Zheng; Jin-Zhong Xu; Pin-Mei Wang (Current Microbiology, 2020)

Integrated control of potato late blight with a combination of the photosynthetic bacterium Rhodopseudomonas palustris strain GJ-22 and fungicides - Xin Zhang; Xiaonian Li; Yu Zhang; Yue Chen; Xinqiu Tan; Pin Su; Deyong Zhang; Yong Liu (BioControl, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Transnasal endoscopic treatment on a rare case of intracranial penetrating brain injury - Min Xu; Yu Luo; Pin Chen; Pan Yi; Cun-zu Wang (Acta Neurologica Belgica, 2020)

Particulates and particulates-bound mercury (Hg(p)) sizes (PM18, PM10, PM2.5, PM1, PM<1) distributions study by using MOUDI sampler at a complex sampling site - Guor-Cheng Fang; Chao-Lang Kao; Pin-Wen Huang; Huang-Min Chen; Yu-Lun Wu; Gui-Ren Liang (Environmental Geochemistry and Health, 2020)

LncRNA TUG1 promoted osteogenic differentiation through promoting bFGF ubiquitination - Yang Yu; Ying Chen; Yi-jing Zheng; Qi-hao Weng; Si-pin Zhu; Dong-sheng Zhou (In Vitro Cellular & Developmental Biology - Animal, 2020)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Anti-Oxidative Effects of Melatonin Receptor Agonist and Omega-3 Polyunsaturated Fatty Acids in Neuronal SH-SY5Y Cells: Deciphering Synergic Effects on Anti-Depressant Mechanisms - Senthil Kumaran Satyanarayanan; Yin-Hwa Shih; Yu-Chuan Chien; Shih-Yi Huang; Piotr Gałecki; Siegfried Kasper; Jane Pei-Chen Chang; Kuan-Pin Su (Molecular Neurobiology, 2018)

Cytochrome P450 2AA molecular clone, expression pattern, and different regulation by fish oil and lard oil in diets of grass carp (Ctenopharyngodon idella) - Xiao-chen Shi; Jian Sun; Ai Jin; Hong Ji; Hai-bo Yu; Yang Li; Xue-xian Li; Pin Liu; Chao Li; Ji-qin Huang (Fish Physiology and Biochemistry, 2018)

Molecular surveillance of Vittaforma-like microsporidia by a small-volume procedure in drinking water source in Taiwan: evidence for diverse and emergent pathogens - Jung-Sheng Chen; Bing-Mu Hsu; Hsin-Chi Tsai; Yu-Pin Chen; Tung-Yi Huang; Kuan-Ying Li; Dar-Der Ji; Herng-Sheng Lee (Environmental Science and Pollution Research, 2018)

Photocatalytic decomposition of indoor ozone motivated by the white-light-emitting diode - Jia-You Gong; Yen-Chi Chen; Kuo-Pin Yu (Clean Technologies and Environmental Policy, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Estimation of students’ exposure to metal concentrations from river-dust episodes during 1994–2012 - Hao-Jan Yang; Szu-Chieh Chen; Chiung-Wen Hu; Yi-Chen Chiang; Ching-Tsan Tsai; Pin-Yu Lin; Dian-Jheng Lai; Chung-Yih Kuo (Environmental Science and Pollution Research, 2017)

A high throughput method for rapid screening of chitosanase-producing fungal strain under acidic conditions - Su Ding; Gui-Guang Chen; Zhi-Qun Liang; Wei Zeng; Mu-Ming Cao; Guo-Pin Chen; Shu-Yu Xie; Wei Li (World Journal of Microbiology and Biotechnology, 2016)

Erratum to: The phylogenetic and recombinational analysis of beak and feather disease virus Taiwan isolates - Shr-Wei Huang; Yu-Chung Chiang; Chien-Yu Chin; Pin-Chi Tang; Pan-Chen Liu; Chi-Young Wang (Archives of Virology, 2016)

The phylogenetic and recombinational analysis of beak and feather disease virus Taiwan isolates - Shr-Wei Huang; Yu-Chung Chiang; Chien-Yu Chin; Pin-Chi Tang; Pan-Chen Liu; Chi-Young Wang (Archives of Virology, 2016)

Imaging Rainfall Infiltration Processes with the Time-Lapse Electrical Resistivity Imaging Method - Gang Zhang; Gui-Bin Zhang; Chien-chih Chen; Ping-Yu Chang; Tzu-Pin Wang; Horng-Yuan Yen; Jia-Jyun Dong; Chuen-Fa Ni; Su-Chin Chen; Chao-Wei Chen; Zheng-yuan Jia (Pure and Applied Geophysics, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

The assessment of high recharge areas using DO indicators and recharge potential analysis: a case study of Taiwan’s Pingtung plain - Jui-Pin Tsai; Yu-Wen Chen; Liang-Cheng Chang; Wen-Fu Chen; Chung-Jung Chiang; You-Cheng Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Analysis of space–time patterns of rainfall events during 1996–2008 in Yilan County (Taiwan) - Hwa-Lung Yu; Bo-Lin Chen; Chuan-Hung Chiu; Mong-Ming Lu; Ching-pin Tung (Stochastic Environmental Research and Risk Assessment, 2015)

Probabilistic framework for assessing the arsenic exposure risk from cooked fish consumption - Min-Pei Ling; Chiu-Hua Wu; Szu-Chieh Chen; Wei-Yu Chen; Chia-Pin Chio; Yi-Hsien Cheng; Chung-Min Liao (Environmental Geochemistry and Health, 2014)

Response to “Letter to editor re: Ling et al. 2011 (Environ Sci Pollut Res Int 18(6): 877–889)” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Dr. Luca Giannini’s Letter to the Editor” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Letter to Editor: Inappropriate exposure data and misleading calculations invalidate the estimates of health risk for airborne titanium dioxide and carbon black nanoparticle exposures in the workplace” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

A new viewpoint on risk control decision models for natural disasters - Chun-Pin Tseng; Cheng-Wu Chen; Yu-Ping Tu (Natural Hazards, 2011)

Structural Characterization of Extracellular Polysaccharides Produced by the Marine Fungus Epicoccum nigrum JJY-40 and Their Antioxidant Activities - Hai-Hong Sun; Wen-Jun Mao; Jie-Ying Jiao; Jia-Chao Xu; Hong-Yan Li; Yin Chen; Xiao-Hui Qi; Yan-Li Chen; Jian Xu; Chun-Qi Zhao; Yu-Jiao Hou; Yu-Pin Yang (Marine Biotechnology, 2011)

Assessing the potential exposure risk and control for airborne titanium dioxide and carbon black nanoparticles in the workplace - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2011)

Using a hybrid approach to optimize experimental network design for aquifer parameter identification - Liang-Cheng Chang; Hone-Jay Chu; Yu-Pin Lin; Yu-Wen Chen (Environmental Monitoring and Assessment, 2010)

Application of System Dynamics on Shallow Multipurpose Artificial Lakes: A Case Study of Detention Pond at Tainan, Taiwan - Hone-Jay Chu; Liang-Cheng Chang; Yu-Pin Lin; Yung-Chieh Wang; Yu-Wen Chen (Environmental Modeling & Assessment, 2010)

Joint Impact of Scaling and Hysteresis on NAPL Flow Simulation - Hung-Hui Chen; Liang-Cheng Chang; Hsin-Yu Shan; Jui-Pin Tsai (Environmental Modeling & Assessment, 2009)

Serial cytokine levels in patients with severe sepsis - Huang-Pin Wu; Chian-Kuang Chen; Kong Chung; Jo-Chi Tseng; Chung-Ching Hua; Yu-Chih Liu; Duen-Yau Chuang; Chung-Han Yang (Inflammation Research, 2009)

Differential global genomic changes in rice root in response to low-, middle-, and high-osmotic stresses - Ting-chen Ma; Rong-jun Chen; Rong-rong Yu; Han-lai Zeng; Duan-pin Zhang (Acta Physiologiae Plantarum, 2009)

Effects of magnesium sulfate on dynamic changes of brain glucose and its metabolites during a short-term forced swimming in gerbils - Shiu-Min Cheng; Dar-Yu Yang; Chien-Pin Lee; Hung-Chuan Pan; Mao-Tsun Lin; Ssu-Hua Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2007)

Assessing Impacts of Typhoons and the Chi-Chi Earthquake on Chenyulan Watershed Landscape Pattern in Central Taiwan Using Landscape Metrics - Yu-pin Lin; Tsun-kuo Chang; Chen-fa Wu; Te-chih Chiang; Shin-hwei Lin (Environmental Management, 2006)

Using the Selective Ion Exchange Resin Extraction and XANES Methods to Evaluate the Effect of Compost Amendments on Soil Chromium(VI) Phytotoxicity - Dar-Yuan Lee; Yu-Na Shih; Hsiu-Ching Zheng; Chiou-Pin Chen; Kai-Wei Juang; Jyh-Fu Lee; Lo Tsui (Plant and Soil, 2006)